A comprehensive finite element model for studying Cochlear-Vestibular interaction. Issue 2 (3rd February 2022) - Liang, Junfeng; Ke, Zhang; Welch, Paige V.; Gan, Rong Z.; Dai, Chenkai
Abstract: We present a 3-D finite element (FE) model of the chinchilla's inner ear consisting of the entire cochlea structure and the vestibular system. The reaction of the basilar membrane to the head rotation and the reaction of ampulla to the stapes movement were investigated. These results demonstrate the existence of hearing-vestibular system interaction. They provide an explanation to the clinical finding on the coexistence between hearing loss and equilibration dysfunction. It is a preliminary, yet critical step toward the development of a comprehensive FE model of an entire ear for mechano-acoustic analysis.